2014
DOI: 10.1371/journal.pone.0113477
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Attachment and Differentiation on Titania Nanotubes Exposed to Air- or Nitrogen-Based Non-Thermal Atmospheric Pressure Plasma

Abstract: The surface topography and chemistry of titanium implants are important factors for successful osseointegration. However, chemical modification of an implant surface using currently available methods often results in the disruption of topographical features and the loss of beneficial effects during the shelf life of the implant. Therefore, the aim of this study was to apply the recently highlighted portable non-thermal atmospheric pressure plasma jet (NTAPPJ), elicited from one of two different gas sources (ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…The above results show that the better hydrophilicity of the materials prepared by a given technology, the higher the corresponding biological properties are. Hydrophilic surfaces were shown to promote the adhesion, proliferation, and differentiation of osteoblasts on the surface of Ti discs, and the results are the same as those in the previous study [25]. It is worth pointing out that for the SLA/NaOH-10s and SLA-PECVD/NaOH-10s groups, the MTT values of SLA/NaOH-10s were less than those of SLA-PECVD/NaOH-10s, although SLA/NaOH-10s were more hydrophilic than SLA-PECVD/NaOH-10s.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The above results show that the better hydrophilicity of the materials prepared by a given technology, the higher the corresponding biological properties are. Hydrophilic surfaces were shown to promote the adhesion, proliferation, and differentiation of osteoblasts on the surface of Ti discs, and the results are the same as those in the previous study [25]. It is worth pointing out that for the SLA/NaOH-10s and SLA-PECVD/NaOH-10s groups, the MTT values of SLA/NaOH-10s were less than those of SLA-PECVD/NaOH-10s, although SLA/NaOH-10s were more hydrophilic than SLA-PECVD/NaOH-10s.…”
Section: Discussionsupporting
confidence: 84%
“…SPSS 17.0 software was used for all statistical analyses. Based on the results from previous studies [24][25][26][27], data from at least three independent experiments were used. Group means and standard deviations were used to calculate each parameter.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that BMSCs attached more to the 6‐hour acid‐treated dentin and exhibited a more outstretched appearance compared with that of HA. This observation is consistent with contact angle assay and suggested an early cell attachment in vivo, which is of vital importance for the initiation of the regeneration progress 44 …”
Section: Discussionsupporting
confidence: 90%
“…This observation is consistent with contact angle assay and suggested an early cell attachment in vivo, which is of vital importance for the initiation of the regeneration progress. 44 In this study, the periodontal defect is induced in the canine model. The protocol was similar to most Class II furcation defects around dog molars.…”
Section: Discussionmentioning
confidence: 99%
“…It also should be noted that the mechanism of cell adhesion is driven by promoting the adsorption of selected proteins (such as a high-molecular-weight nanometer-sized glycoprotein fibronectin), which are important for integrin-mediated communication between cells and surface. Oh et al [44] assumed that flat Ti had a lower population of fibronectin aggregates due to its lower hydrophilicity in comparison with higher-surface-area TNTs surfaces, the latter was shown by water droplet contact angle tests [16,33,45,46]. Moreover, the efficiency of fibronectin adhesion to TNTs surfaces varies depending on the size of TNTs pores.…”
Section: Discussionmentioning
confidence: 99%